Testosterone reduces uterine contractions in vivo: Evidence for non-genomic action in rats - Saif-alnasr H. Mohammed; Mohammed Taj-Eldin Abdalla; Ayman B. Mousa; Anita Sztojkov-Ivanov; Kálmán Ferenc Szűcs; Róbert Gáspár (PLoS ONE, 2026)
This study aimed to investigate the non-genomic effect of testosterone (T) on uterine muscle contractility in non-pregnant and 22 nd day pregnant rats, in vivo. It provides the first evidence of an in vivo T uterine relaxation effect during pregnancy. Circulating T levels were measured within 8 hours after a single intraperitoneal (ip) administration of T (10 mg/kg) by ELISA. The kinetic curves of a single dose of T (10 mg/kg of ip) were estimated for 8 hours; plasma T was measured using ELISA kits. The rapid in vivo action of T was studied by measuring contractions using strain-gauge sensors in 15-minute intervals, and the AUC was calculated. The animals received T alone (3/10/30/100/300 mg/kg ip), with flutamide (100 mg/kg ip), solvent (DMSO+Macrogol 25% + 75%, 1 ml/kg ip) or normal saline (1 ml/kg) (n = 5–8/group, 160–220 g). To verify the possible mechanism of action, we also examined the uterine relaxing effect of T (10 −4 M) and nifedipine (10 −7 M) in vitro on KCl (40 mM)-stimulated contractions by cumulatively increasing the concentration of CaCl 2 (1–120 mM) in the organ bath. Plasma T and 4-hydroxyphenylpyruvate dioxygenase (4-HPPD) levels were measured by ELISA before and 30-minutes after administration (n = 4–8/group, 200–220 g). T had similar half-life and t max values in both non-pregnant and pregnant rats, however, the AUC values were higher in pregnant animals. T (30/100/300 mg/kg single ip dose) elicited a flutamide-resistant dose-dependent uterine relaxing effect in both non-pregnant and 22 nd day pregnant rats. T plasma levels were proportional with the administered doses. 4-HPPD plasma levels remained unchanged in both non-pregnant and 22 nd day pregnant rats after 30 min of T administration. A single dose T induces rapid, non-genomic, dose-dependent uterine relaxation via blocking of calcium effect in non-pregnant and late-pregnant rats in vivo. Based on our results, T or its analogues might be good candidates for further pre-clinical and clinical studies for uterine hyperactivity-related conditions.